The Influence of Product Quality, Price, and Personal Selling on Purchasing Decisions of Loyal Brands at PT Kawi Agung Kencana: The Influence of Product Quality, Price, and Personal Selling on Purchasing Decisions of Loyal Brands at PT Kawi Agung Kencana - Purnama Yanti Purba; Cerrly Riawin; Rini Wijaya; Wenti Suryani; William Andreas (Institute of Computer Science (IOCS), 2020)
The purpose of this study is to examine the effect of Product Quality, Price and Personal Selling on the Purchase Decision of Loyal Brand Contact Stop at PT Kawi Agung Kencana. Decreasing Purchasing Decisions due to Product Quality, Price and Personal Selling. Researchers took a population of 176 customers in this study in 2019. The samples in this study were 122 customers and 30 customers for validity and reliability testing. The sampling technique used was simple random sampling. In this study, data collection related to the problems examined by researchers was carried out by means of questionnaires, interviews and documentation studies. Product Quality has a positive and significant effect on the Purchase Decision of Loyal Brand Contact Stop at PT Kawi Agung Kencana. Price, has a positive and significant effect on the Decision to Purchase Loyal Brand Stop Contacts at PT Kawi Agung Kencana. Personal Selling has a positive and significant effect on the Purchase Decision of Loyal Brand Contact Stop at PT Kawi Agung Kencana. Product Quality, Price, and Personal Selling have a positive and significant effect on the Purchase Decision for Loyal Brand Contact Stop at PT Kawi Agung Kencana.